Total synthesis of angustine and angustoline. Issue 15 (9th April 2020) - Peng, Xin; Fu, Min; Ou, Jingdan; Cao, Ruidi; Song, Hao; Liu, Xiao-Yu; Qin, Yong
Graphical abstract: Abstract: A short total synthesis of the indolopyridine alkaloids angustine (1 ) and angustoline (2 ) has been achieved in five and six steps, respectively. Two key steps for assembly of the pentacyclic core included a Bischler-Napieralski cyclization and a cobalt-catalyzed carbonylative lactamization. A late-stage Mukaiyama hydration allowed the first successful transformation of angustine (1 ) to angustoline (2 ).